Distribution contracts in Europe through the rules of European competition law. The novelties provided by Regulation (EU) 2022/720 on the exemption of vertical agreements - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
On June 1, 2022, Commission Regulation (EU) 2022/720 of 10 May 2022 on the application of Article 101(3) of the Treaty on the Functioning of the European Union to categories of vertical agreements and concerted practices entered into force in the Spanish legal system. This Regulation replaces Regulation 330/2010, which allowed distribution agreements that may contain competition restrictions contrary to article 101.1 TFUE to be exempt from prohibition by meeting the criteria established by the Regulation itself and the Guidelines that accompanied it. At present and until May 31, 2034, the key Regulation to verify whether a distribution contract complies with the rules of European competition law will be the aforementioned Regulation (EU) 2022/720. The objective of this paper is the study of the novelties presented by Regulation 2022/720 compared to its predecessor Regulation 330/2010.
Keywords: Vertical agreement; European competition Law; distribution agreements; luxury products; competition restraints